Empirically defining rapid response to intensive treatment to maximize prognostic utility for bulimia nervosa and purging disorder. (May 2015) - MacDonald, Danielle E.; Trottier, Kathryn; McFarlane, Traci; Olmsted, Marion P.
Abstract: Rapid response (RR) to eating disorder treatment has been reliably identified as a predictor of post-treatment and sustained remission, but its definition has varied widely. Although signal detection methods have been used to empirically define RR thresholds in outpatient settings, RR to intensive treatment has not been investigated. This study investigated the optimal definition of RR to day hospital treatment for bulimia nervosa and purging disorder. Participants were 158 patients who completed ≥6 weeks of day hospital treatment. Receiver operating characteristic (ROC) analysis was used to create four definitions of RR that could differentiate between remission and nonremission at the end of treatment. Definitions were based on binge/vomit episode frequency or percent reduction from pre-treatment, during either the first four or first two weeks of treatment. All definitions were associated with higher remission rates in rapid compared to nonrapid responders. Only one definition (i.e., ≤3 episodes in the first four weeks of treatment) predicted sustained remission (versus relapse) at 6- and 12-month follow-up. These findings provide an empirically derived definition of RR to intensive eating disorder treatment, and provide further evidence that early change is an important prognostic indicator. Highlights: This study empirically defined rapid response to intensive treatment for bulimia. Receiver operating characteristic analysis was used. Binge/vomit symptoms in the first weeks discriminated remission status. ≤3 episodes in the first 4 weeks was the optimal definition of rapid response. Rapid responders were less likely to relapse up to 12 months post-treatment.